Crack-containing hot-stamped coated steel component with excellent spot weldability and excellent spray adhesion
By applying an optimized aluminum alloy coating on the steel substrate of hot stamping steel parts and adjusting the hot stamping process parameters, the problem of difficult to take into account both spray adhesion and spot welding properties in the prior art is solved, and the excellent performance of the parts is achieved .
Patent Information
- Application Number
- CN202480001267.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-02-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-02-09
AI Technical Summary
When existing hot stamped steel parts improve spray adhesion, spot welding properties often damage, making it difficult to achieve excellent spray adhesion and spot welding properties at the same time.
By applying an optimized aluminum alloy coating on at least one surface of the steel substrate, the crack density of the coating is controlled and process parameters such as heating rate and austenitization parameters are adjusted during the hot stamping process to ensure the coating's Continuity and form.
Excellent spray adhesion and spot weldability of hot stamped coated steel parts are achieved, ensuring high performance of the parts in use.
Smart Images

Figure CN119421784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hot stamping coated steel component, which comprises a steel substrate and an aluminum alloy coating on at least one surface of the steel substrate, the coating comprising an optimized crack density, the component having excellent spray adhesion and excellent spot weldability. The present invention also relates to a method for manufacturing the hot stamping coated steel component. Background Art
[0002] Such components can also be used, for example, in the automotive industry for the production of structural elements for an anti-intrusion function or an energy absorption function.
[0003] In this type of application, it is desirable to have steel parts that combine high mechanical strength, high impact resistance, good corrosion resistance and dimensional accuracy. These properties are particularly required for automotive parts such as front or rear rails, roof rails, B-pillars and chassis parts such as lower control arms, engine mounts.
[0004] In order to meet these needs, these parts are now usually produced by hot stamping process (also called press hardening). In the hot stamping process, as disclosed in particular in FR 2 780 984 and FR 2 807 447, a blank cut from a steel plate and pre-coated with a metal or metal alloy is heated in a furnace to a temperature at which the ferrite and cementite microstructure of the low carbon steel are at least partially converted into austenite, and then the blank is hot stamped in a die. During stamping, the part is kept in the die to achieve rapid cooling, thereby resulting in the formation of the desired hardened microstructure and obtaining the desired mechanical properties. The pre-coating layer can be aluminum or an aluminum alloy. During heating in the furnace, the pre-coating alloy forms a compound with the steel substrate that protects the steel surface from decarburization and scale formation.
[0005] Recently, the focus has been on coating components after hot stamping and how the coating affects the performance of the component in service.
[0006] In WO 2008 / 053273 A1 it is proposed to limit the pre-coating thickness at each location to between 20 μm and 33 μm and to control the hot stamping process, in particular the heating rate and austenitizing parameters, in order to achieve a favourable continuity and morphology of successive layers in the component coating, leading to improved weldability.
[0007] However, it remains desirable to provide a hot stamped steel component having further improved spot weldability and improved spray adhesion which can be produced with a wider range of pre-coating thicknesses.
[0008] In particular, the present inventors have found that even though spray adhesion can be improved in some cases, such improvement is at the expense of spot weldability, and thus it is still desirable to provide a component that combines excellent spray adhesion and excellent spot weldability. Summary of the invention
[0009] Therefore, the present invention aims to provide a hot stamping coated steel component and a method for manufacturing the hot stamping coated steel component, the hot stamping coated steel component comprising a steel substrate and an aluminum alloy coating on at least one surface of the steel substrate, the hot stamping coated steel component having both excellent spray adhesion and excellent spot weldability.
[0010] In particular, it is desirable to provide a hot stamped coated steel part comprising at least one undeformed portion having a welding range greater than 1 kA as measured according to standard SEP 1220-2 (2011) and excellent spray adhesion. The spray adhesion is evaluated by performing a dry spray test and a wet spray adhesion test according to standard ISO 2409:2013. The spray adhesion is considered to be excellent if the result of the dry spray test is strictly lower than 1 and the result of the wet spray adhesion test is lower than or equal to 1.
[0011] For this purpose, the invention relates to a hot stamped coated steel component according to claim 1 .
[0012] The hot stamped coated steel component preferably has one or more of the features of claims 2 to 13 .
[0013] The invention also relates to a method for producing a hot stamped coated steel component according to claim 14 .
[0014] The method preferably comprises one or more of the features of claims 15 to 24 .
[0015] The invention also relates to the use of a hot stamped coated steel component according to the invention or produced by a method according to the invention for producing chassis or body-in-white components or suspension arms of a motor vehicle. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The invention will now be described and illustrated in detail by way of example without introducing limitations, in view of the accompanying drawings, in which:
[0017] - Figure 1 An example of a hot stamped coated steel component according to the invention is schematically illustrated,
[0018] - Figure 2 is the cross section of the coating in the undeformed part of the component according to the invention as observed in a given field of view,
[0019] - Figure 3 An example of a cross section of a coating in an undeformed portion of a comparative component is shown, in which no cracks are present. DETAILED DESCRIPTION
[0020] The present invention relates to hot stamping coated steel parts.
[0021] Hot stamped coated steel parts are non-planar parts produced by hot stamping blanks.
[0022] Steel plate refers to a flat steel plate. Steel plate here refers to a hot-rolled steel plate or a cold-rolled steel plate in the form of a coil or cut from such a coil.
[0023] The steel plate has a top face and a bottom face, which are also referred to as top side and bottom side or as top face and bottom face or top surface and bottom surface. The distance between the faces is designated as the thickness of the plate. The thickness can be measured using, for example, a micrometer, the spindle and anvil of which are placed on the top and bottom faces, the axis between the spindle and the anvil being perpendicular to the plate surface. In a similar manner, the thickness can also be measured on a formed part. In a similar manner, the thickness can also be measured on a blank and a part.
[0024] A steel blank is a flat steel sheet which has been cut into any shape suitable for its use, or a blank which is produced by cutting two or more steel sheet materials, possibly of different thickness or composition, into the desired shape and assembling them together, in particular welding them.
[0025] The average thickness of a component or the average thickness of a portion of a component refers to the overall average thickness of the material making up the component after it has been formed from an initially flat sheet into a three-dimensional component.
[0026] Uniform thickness means that the thickness of the blank, component, plate or region or portion thereof under consideration is constant, the maximum variation of the thickness of the blank, component, plate or region or portion thereof being at most 0.1 mm above or below the average thickness of the blank, component, plate or region or portion. In particular, uniform thickness means that no thickness variations are automatically introduced during production, in particular during production of plates in hot and / or cold rolling and during forming operations in component production.
[0027] In the following, the thickness of a blank, component, plate or a region or portion thereof having a uniform thickness is defined as the average thickness of the blank, component, plate or a region or portion thereof.
[0028] Furthermore, the term "thickness" is used to refer to the thickness of a blank, component, panel, or region or portion thereof of uniform thickness, whereby "average thickness" is more generally used to refer to the average thickness of a blank, component, panel, or region or portion thereof, whether the thickness is uniform or variable.
[0029] Custom welded blanks are made by assembling together, for example by laser welding, several steel sheets or cut steel blanks, called sub-blanks, to optimize the performance of the component in different areas thereof, thereby reducing overall component weight, overall component cost, and material waste. The sub-blanks that form the custom welded blank can be assembled with or without overlap, for example, the sub-blanks can be laser butt welded (without overlap), or the sub-blanks can be spot welded to each other (with overlap).
[0030] A flexible blank is a custom welded blank comprising regions where at least part of the connection between the different sub-blanks is not rigid, thereby allowing the sub-blanks to move in different directions during the forming operation of the corresponding regions.
[0031] In contrast to a custom welded blank, a monolithic blank is a blank that includes one single sub-blank, rather than several sub-blanks combined together.
[0032] A tailor-made rolled blank is a blank having a varying thickness, ie a thickness variation along the blank, obtained by differential rolling during the steel plate production process.
[0033] Hot stamping is a forming technique that involves heating a blank to a temperature at which the microstructure of the steel is at least partially transformed into austenite, thereby forming the blank at high temperature by stamping it, and quenching the formed part to obtain a microstructure with high strength. Hot stamping allows obtaining very high-strength parts with complex shapes and presents many technical advantages.
[0034] Monolithic components are hot stamped parts produced from a monolithic blank.
[0035] The integral component is produced, for example, from an integral blank having a uniform thickness, or from an integral custom-made rolled blank.
[0036] A hot stamped welded steel component or a hot stamped laser welded steel component is a hot stamped component produced from a custom welded blank, such as a flexible blank. Thus, the hot stamped welded steel component comprises two or more hot stamped subcomponents and one or more hot stamped welds that join the hot stamped subcomponents together.
[0037] In an embodiment, the hot stamped coated steel component of the present invention is a unitary component.
[0038] In another embodiment, the hot stamped coated steel component is a hot stamped welded steel component.
[0039] The hot stamped coated steel component of the present invention preferably has an average thickness e comprised between 0.6 mm and 3.5 mm. P .
[0040] The range of 0.6 mm to 3.5 mm is a common thickness used in the manufacture of structural components or reinforcement components for the automotive industry. This thickness range is also suitable for industrial press hardening tools, especially hot stamping presses or dies.
[0041] Additionally, as discussed in detail below, the heat treatment applied to a given steel sheet thickness has an effect on the coating, particularly on the formation of cracks in the coating in the flat, undeformed portions desired by the present invention.
[0042] Preferably, the average thickness e of the hot stamped coated steel part is P In the range of 0.7mm to 3.0mm.
[0043] In an embodiment, the hot stamped coated steel component has a uniform thickness e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. P .
[0044] In another embodiment, the hot stamped coated steel component has a variable thickness (and therefore non-uniform). In this case, the hot stamped coated steel component includes a uniform thickness having different Pi Two or more regions of different uniform thickness e Pi Preferably, each is 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm.
[0045] As an example, hot stamped coated steel parts with variable thickness may be produced from tailor-made rolled blanks with varying thickness obtained by differential rolling during the steel plate production process.
[0046] As another example, the hot stamped coated steel component having a variable thickness may be a hot stamped welded steel component produced by custom welding blanks made from blanks having different thicknesses.
[0047] The hot stamped coated steel component comprises a steel substrate (also referred to as a steel base) having two major faces.
[0048] The steel in the substrate is a steel for hot stamping, ie a steel that can be hardened after austenitizing and cooled rapidly by quenching.
[0049] In an embodiment, the component is produced from a monolithic blank and the steel substrate is made from a single piece of steel.
[0050] In another embodiment, the component is a hot stamped welded steel component and the steel substrate includes two or more regions (or subcomponents) that may be made of the same steel or different steels and may have the same or different microstructures.
[0051] In the following, the steel microstructure and composition of a steel substrate refers to the microstructure and composition of the steel substrate (if the substrate is made of a single steel) or the microstructure or composition of one or more of the regions or sub-portions of the steel substrate.
[0052] The composition of the steel depends on the desired mechanical properties of the component. However, preferably, in the steel matrix or in each region of the steel matrix, the steel has a composition comprising in weight %:
[0053] 0.062%≤C≤0.4%
[0054] 0.4%≤Mn≤3.9%
[0055] 0.10%≤Si≤1.5%
[0056] 0.005%≤Al≤1.0%
[0057] 0.001%≤Cr≤2.0%
[0058] 0.001%≤Ti≤0.2%
[0059] 0.0005%≤B≤0.010%
[0060] Ni≤2%
[0061] Nb≤0.1%
[0062] Mo≤0.65%
[0063] W≤0.30%
[0064] N≤0.010%
[0065] 0.0001%≤S≤0.05%
[0066] 0.0001%≤P≤0.1%
[0067] Ca≤0.005%,
[0068] The balance of the composition comprises iron and unavoidable impurities resulting from refining.
[0069] The level of impurities produced by the refining process will depend on the production route used. For example, when a blast furnace route with low steel scrap (recycled steel) levels is used, the impurity levels will remain very low. On the other hand, when an electric furnace is used to refine steel with a very high rate of recycled scrap steel, the impurity levels will increase significantly. For example, in the case of using an electric furnace to refine steel with a very high rate of recycled scrap steel, the level of Cu can rise to 0.25%, the level of Ni can rise to 0.25%, the level of Sn can rise to 0.05%, the level of As can rise to 0.03%, the level of Sb can rise to 0.03%, and the level of Pb can rise to 0.03%.
[0070] Therefore, in an embodiment, the steel contains up to 0.25% Cu, up to 0.05% Sn, up to 0.03% As, up to 0.03% Sb and / or up to 0.03% Pb as unavoidable impurities.
[0071] The above composition is conducive to achieving high mechanical properties, especially a tensile strength TS in the range of 950 MPa to 2100 MPa.
[0072] The tensile strength is measured according to ISO standard NF EN ISO 6892-1 published in October 2009. The tensile test specimens are cut from the flat part of the hot stamped part.
[0073] Hereinafter, unless otherwise specified, the contents of elements are expressed in weight percent.
[0074] The carbon content depends on the desired tensile strength TS of the hot stamped coated steel component.
[0075] Below a C content of 0.062%, it is difficult to obtain a tensile strength of at least 950 MPa after hot stamping under any cooling conditions. Above 0.4%, in combination with other elements of the composition, the adhesion of the coating after hot stamping may be unsatisfactory, and the delayed cracking resistance and toughness of the steel are reduced. In an embodiment, the C content is at most 0.38%.
[0076] The C content depends on the desired tensile strength TS of the hot stamped part produced by hot stamping the steel sheet. In an embodiment, the C content is included between 0.062% and 0.095%. If a higher tensile strength, about 1500 MPa, is desired, the C content can be increased to a range of 0.15% to 0.30%. If the tensile strength needs to be further increased to at least 1800 MPa, the C content can be added at a content of up to 0.4%.
[0077] In addition to its deoxidizing effect, manganese has an important influence on hardenability, especially when the manganese content is at least 0.4%. Above 3.9%, Mn may be too important for the stability of austenite, which leads to the formation of too pronounced banded structures. Preferably, the Mn content is at most 3.0%.
[0078] Silicon is added in an amount of at least 0.10% to assist in deoxidation of the liquid steel and to assist in hardening of the steel by precipitation in solid solution. However, the silicon content is usually limited to avoid excessive formation of silicon oxide which would impair the coatability of the steel. Therefore, the silicon content is usually less than or equal to 1.5%, for example less than or equal to 0.80%.
[0079] Aluminum can be added as a deoxidizer in a content of at least 0.005%. In addition, if the titanium content is insufficient, aluminum can protect boron by combining with N. The Al content is preferably at least 0.01%. The Al content is generally lower than or equal to 1.0% to avoid oxidation problems and to avoid the formation of ferrite during hot stamping. Preferably, the Al content is at most 0.1%.
[0080] Cr can be added to increase the hardenability of the steel and help obtain the desired tensile strength after hot stamping. When Cr is added, the Cr content is higher than or equal to 0.01%, preferably higher than or equal to 0.1%, up to 2.0%. If active Cr addition is not performed, the Cr content may be present as an impurity at a content as low as 0.001%.
[0081] When titanium is added, the content of titanium is preferably at least 0.008% and at most 0.2%. When the Ti content is included between 0.008% and 0.2%, precipitation at very high temperatures occurs in the form of TiN, and then precipitation at lower temperatures occurs in the form of fine TiC in austenite, resulting in hardening. In addition, when titanium is added in addition to boron, titanium prevents the combination of boron with nitrogen, which combines with titanium. Therefore, the titanium content is preferably higher than 3.42*N, N being the N content expressed as a weight percentage in the composition. However, the Ti content should preferably be kept below or equal to 0.2%, preferably below or equal to 0.1%, more preferably at most 0.05%, in order to avoid the precipitation of coarse TiN precipitates. If active addition of Ti is not performed, Ti is present as an impurity in a content of at least 0.001%.
[0082] Boron is added in a content of at least 0.0005% and at most 0.010% to increase the hardenability of the steel. Preferably, the B content is at most 0.004%.
[0083] In an embodiment, Ni may be added in an amount of up to 2% and typically at least 0.25% and preferably up to 0.5% to reduce the sensitivity to delayed fracture by concentrating on the surface of the component. If not added, Ni may be present as an impurity in amounts as low as 0.001%. Depending on the production route used, the Ni content as an impurity may be as high as 0.25% (for example when a high proportion of recycled scrap steel is used to produce steel) or as high as 0.1% (for example when lower levels of steel scrap are used).
[0084] Optionally, up to 0.1% niobium is added to provide precipitation hardening and microstructural refinement, such as prior austenite grain size. Nb further improves the ductility of the steel. When Nb is added, the Nb content is preferably at least 0.01%. The Nb content is preferably at most 0.06% to avoid the formation of coarse (Ti, Nb)(C, N) precipitates.
[0085] Molybdenum can be added in an amount of up to 0.65%. When Mo is added, the content of Mo is preferably at least 0.05%. Mo is preferably added together with Nb and Ti to form a very stable eutectoid at high temperatures. Mo can also be added to increase the toughness of the steel, thereby acting as a grain boundary strengthener in the solid solution state. The best effect is obtained when the Mo content is comprised between 0.15% and 0.25%.
[0086] W may be added to improve the hardenability and hardenability of steel by forming tungsten carbide. When W is added, the content of W is higher than or equal to 0.001% and lower than or equal to 0.30%.
[0087] Sulfur, phosphorus and nitrogen are usually present in steel compositions as impurities.
[0088] The nitrogen content is usually at least 0.0005%. The N content is usually at most 0.010%, preferably at most 0.005%, to prevent the precipitation of coarse TiN precipitates.
[0089] When in excess, sulfur and phosphorus reduce ductility. Therefore, the content of sulfur and phosphorus is limited to 0.05% and 0.1%, respectively.
[0090] In particular, the presence of S in the liquid steel leads to the formation of MnS precipitates which are detrimental to the properties. Preferably, the S content is at most 0.01%, most preferably at most 0.005%. Achieving very low S contents, i.e. S contents below 0.0001%, is very expensive and does not provide any benefit. Therefore, the S content is usually higher than or equal to 0.0001%.
[0091] Preferably, the phosphorus content is at most 0.05%, more preferably at most 0.02%. It is very expensive to achieve very low P contents, ie below 0.0001%. Therefore, the P content is usually higher than or equal to 0.0001%.
[0092] The steel may be subjected to a spheroidizing treatment of sulfides using calcium, which has the effect of improving the bending angle due to the spheroidization of MnS. Therefore, the steel composition may contain at least 0.0001% and at most 0.005% of Ca.
[0093] The remainder of the steel composition is iron and impurities resulting from the refining process. As described above, the impurities resulting from the refining process may include 0.25% or less Cu, 0.05% or less Sn, 0.03% or less As, 0.03% or less Sb and / or 0.03% or less Pb.
[0094] The composition of the steel can be selected according to the desired mechanical properties, in particular with regard to strength and ductility.
[0095] In particular, when a tensile strength in the range of 950 MPa to 1200 MPa and a bending angle above 75° (measured according to VDA 238-100 bending standard July 2020) is desired, the steel substrate or the steel in at least one area of the steel substrate in the entire component or in at least one area of the component preferably has a composition according to the first preferred composition comprising in wt. %:
[0096] 0.062%≤C≤0.095%
[0097] 1.4%≤Mn≤1.9%
[0098] 0.2%≤Si≤0.5%
[0099] 0.020%≤Al≤0.070%
[0100] 0.02%≤Cr≤0.1%
[0101] Among them, 1.5%≤(C+Mn+Si+Cr)≤2.7%
[0102] 0.0035%≤Ti≤0.072%
[0103] 0.0002%≤B≤0.004%
[0104] 0.04%≤Nb≤0.06%
[0105] Among them, 0.044%≤(Nb+Ti)≤0.09%
[0106] 0.001%≤N≤0.009%
[0107] 0.0005%≤S≤0.003%
[0108] 0.0001%≤P≤0.020%
[0109] Ca≤0.005%,
[0110] The balance of the composition comprises iron and unavoidable impurities resulting from refining.
[0111] On the other hand, when a tensile strength of at least 1400 MPa is required, the steel substrate or the steel in at least one region of the steel substrate preferably has a composition according to the second preferred composition comprising in wt %:
[0112] 0.15%≤C≤0.30%
[0113] 0.5%≤Mn≤3.0%
[0114] 0.10%≤Si≤0.50%
[0115] 0.005%≤Al≤0.1%
[0116] 0.01%≤Cr≤1.0%
[0117] 0.001%≤Ti≤0.2%
[0118] 0.0002%≤B≤0.010%
[0119] 0.0005%≤N≤0.010%
[0120] 0.0001%≤S≤0.05%
[0121] 0.0001%≤P≤0.1%
[0122] Ca≤0.005%,
[0123] The remainder is Fe and unavoidable impurities resulting from refining.
[0124] If an even higher tensile strength of 1800 MPa or above is required, the composition of the steel substrate or at least one region of the steel substrate preferably comprises, according to the third preferred composition, the following in wt. %:
[0125] 0.3%≤C≤0.4%
[0126] 0.5%≤Mn≤1.0%
[0127] 0.40%≤Si≤0.80%
[0128] 0.01%≤Al≤0.1%
[0129] 0.1%≤Cr≤1.0%
[0130] 0.008%≤Ti≤0.03%
[0131] 0.0005%≤B≤0.003%
[0132] Ni≤0.5%
[0133] 0.01%≤Nb≤0.1%
[0134] 0.1%≤Mo≤0.5%
[0135] N≤0.005%
[0136] 0.0001%≤S≤0.004%
[0137] 0.0001%≤P≤0.02%
[0138] Ca≤0.0010%,
[0139] The balance of the composition comprises iron and unavoidable impurities resulting from refining.
[0140] The steel substrate of the hot stamped coated steel component generally has a microstructure comprising, by volume fraction, at least 60% martensite, at most 20% bainite and at most 5% ferrite and at most 15% austenite.
[0141] The martensite fraction may be as high as 100%, while the bainite fraction, ferrite fraction, and austenite fraction may each be as low as 0%.
[0142] This microstructure description applies to most steel substrates, meaning that this microstructure is present in at least 95% of the volume of the steel substrate, preferably in the entire volume of the steel substrate.
[0143] The microstructure is determined by the following method: a specimen is cut from a hot stamped coated steel part, polished as detailed below, and etched with Nital 2% (10s) to reveal the microstructure. The section is then examined by an optical microscope with a magnification of 500x, and if it is necessary to distinguish between martensite and bainite, a scanning electron microscope (SEM) is used (backscattered electron mode, magnification 500x, EHT (electron high voltage voltage) = 15.00 kV, scale 10 microns). The volume fraction of each component (martensite, bainite, ferrite, austenite) is determined by image analysis by a method known per se.
[0144] In an embodiment, the austenite fraction is at most 5% by volume and / or the bainite fraction is at most 10% by volume.
[0145] In an embodiment, the microstructure comprises, by volume, at least 80% martensite, at most 10% bainite, at most 5% austenite, and at most 5% ferrite.
[0146] In a preferred embodiment, the microstructure is substantially martensitic, ie comprises at least 95% martensite and at most 5% bainite and / or ferrite by volume.
[0147] More preferably, the microstructure is fully martensitic.
[0148] The hot stamped coated steel component includes an undeformed portion and at least one deformed portion.
[0149] In an embodiment, the hot stamped coated steel component includes two or more undeformed portions.
[0150] In practice, during stamping, in particular hot stamping, to produce a component, one or more portions of the blank are not deformed, while other portions are deformed to achieve the final non-planar geometry of the component. The or each undeformed portion is one that has not undergone a deformation during hot stamping or during a previous cold pre-deformation of the blank, if performed.
[0151] By undeformed, it must be understood that during the stamping process the undeformed part undergoes an equivalent deformation ε of at most 0.01 b The equivalent deformation is limited to Among them, ε1 and ε2 are the main deformations.
[0152] For example, the principal deformations ε1 and ε2 of a given molded part may be determined in the following manner. The procedure described below is one example of a method to determine the principal deformations and is by no means limiting - other methods exist:
[0153] - Acquire a digital model of the physical component using a 3D camera. The output of this first operation is a CAD file representing the physical component.
[0154] -CAD files are then processed by reverse molding software, such as Onestep processing, which calculates the deformation field required to stamp the component shape starting from a flat blank.
[0155] - Then, use the commercial software listed above (such as or ) in any commercial software, the deformation field is represented by the corresponding principal deformations.
[0156] When the above methods cannot be applied, for example because only a part of the fully formed part is available, or in order to assess very local deformations in specific areas, such as on edges, electron backscatter diffraction (EBSD) measurements can be done in combination with scanning electron microscopy (SEM) observations. It relies on the correlation that exists between deformation and local crystal orientation errors. For example, the following reference gives an example of such a measurement: Kamaya M. Assessment of local deformation using EBSD: quantification of accuracy of measurement and definition of local gradient. Ultramicroscopy 2011 Jul; 111(8): 1189-99. doi: 10.1016 / j.ultramic.2011.02.004. Europe 2011 Feb 21. PMID: 21763236.
[0157] Another method that may be applied to determine the primary deformation about a formed part is to measure the thickness of the deformed material in the formed area and compare that thickness to the thickness of the undeformed area.
[0158] The or each undeformed portion is a flat portion of the component.
[0159] The or each undeformed portion is for example a flange of the component or a flat portion between two deformed portions of the component. As an example, the component is hat-shaped and the flat portion may also comprise a flat top portion of a hat-shaped stamped component.
[0160] Figure 1 Examples of such components are illustrated schematically.
[0161] Figure 1 Shown is a hot stamped coated steel component 1 which has been welded to a flat component 2 by means of a plurality of spot welds 3. In this example, the spot welds 3 are located at flanges 8 of the hot stamped coated steel component 1.
[0162] The exemplary hot stamped coated steel component 1 is a hat-shaped component (or "Ω"-shaped component) including a flat top portion 4, two first curved portions 5 (or radii) extending from two opposite longitudinal edges of the flat top portion 4, two side walls 6 each extending from a longitudinal edge of the first curved portion 5, two second curved portions 7 each extending outward from a longitudinal edge of the side walls 6, and two flat flanges 8 each extending from a longitudinal edge of the second curved portion 7 to an outer edge of the component 1. Thus, the flanges 8 form an edge of the component 1.
[0163] In this example, the flange 8 and the flat top portion 4 are flat, undeformed portions of the hot stamped coated steel component 1 .
[0164] The undeformed portions may be distinguished from the deformed portions in terms of their shape and / or by observing cracks in the coating of these portions.
[0165] In fact, as described in detail below, the coating of the deformed portion contains wide cracks which are absent or only rarely present in the coating of the undeformed portion.
[0166] Each undeformed portion, although not subjected to deformation, has been subjected to the same thermal cycle as the deformed portion or portions.
[0167] The hot stamped coated steel component of the present invention is different from a flat blank produced by austenitizing and quenching without any deformation, not only in that the hot stamped coated steel component of the present invention includes at least one deformed portion produced by hot stamping, but also in that the entire hot stamped coated steel component is subjected to a thermal cycle by hot stamping, which is different from the thermal cycle experienced by the undeformed plate.
[0168] In particular, each undeformed portion, although not subjected to deformation, undergoes the same thermal cycle as one or more deformed portions during hot stamping during heating, transfer to the die and retention in the die.
[0169] Thus, in a hot stamped coated steel component, the or each deformed portion is deformed during hot stamping and the or each undeformed portion, although undeformed, is subjected to the same thermal cycle as the deformed portion or portions during hot stamping.
[0170] The hot stamped coated steel part of the invention obtained by the in-die hot stamping process is also different from the samples produced by heating in an experimental furnace or any non-surface contact technique, such as in a Gleeble machine, and uniaxially deformed in the furnace. In fact, such samples have no undeformed parts and are subjected to uniaxial deformation (tensile deformation), whereby in hot stamping the deformation is non-uniform throughout the part and is three-dimensional. In addition, the thermal cycles experienced by the hot stamped coated steel part are different from those experienced in the experimental furnace, which does not involve any transfer or stamping in the mold.
[0171] The or each flat undeformed portion of the component is of uniform thickness e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. pflat part.
[0172] For example, if the flange comprises different thicknesses e pflat(1) and e pflat(2)If there are two regions of the deformation, each of these regions is a different undeformed portion.
[0173] If the hot stamped coated steel component has a uniform thickness, the thickness of the flat undeformed portion (or each undeformed portion) is equal to the thickness e of the hot stamped coated steel component. P .
[0174] If the hot stamped coated steel part has a variable thickness and includes two or more undeformed portions, the undeformed portion is denoted by e pflat(i) The thicknesses of may be different from each other, or may be the same, wherein i=1...n is an index associated with a corresponding undeformed portion, and n is the number of undeformed portions.
[0175] Thickness pflat It can be measured, for example, using a micrometer.
[0176] The hot stamped coated steel component comprises a coating on at least one side of a steel substrate.
[0177] The coating is an aluminum alloy coating.
[0178] The coating comprises aluminum and iron, and preferably also silicon.
[0179] The coating advantageously contains more than 50% aluminium.
[0180] For example, the coating contains 8 wt % to 12 wt % of Si and 3 wt % to 5 wt % of Fe, with the balance being aluminum and inevitable impurities.
[0181] The coating is the result of interdiffusion between the aluminum alloy pre-coating and the steel during hot stamping.
[0182] The coating comprises an interdiffusion layer which is located at the innermost side of the coating, ie in contact with the steel substrate.
[0183] The interdiffusion layer generally has an Fe content of at least 80% and at most 95% and an Al content of 4% to 20% and at most 2% Si.
[0184] In an embodiment, the interdiffusion layer has a composition including 86% to 95% Fe, 4% to 12% Al, and 0% to 2% Si.
[0185] The coating also includes an outer layer extending from the diffusion layer to the surface of the coating.
[0186] The outer layer typically comprises or consists of an intermetallic compound of Fe, Al and possibly Si.
[0187] The outer layer may comprise a single layer, or may itself be composed of sub-layers of different intermetallic compounds.
[0188] For example, the outer layer includes one to four sub-layers.
[0189] However, in the present invention, the inventors have found that, regardless of the layers in the coating, in particular regardless of their composition and number, if the linear density of cracks meets the conditions defined below, the object of the present invention is achieved.
[0190] In the hot stamped coated steel part according to the invention, the total thickness of the coating e coating and the thickness of the interdiffusion layer e IDL The following conditions are met:
[0191] 40≤E pc ≤80
[0192] in,
[0193]
[0194] If E pc Values below 40 may result in the coating not being able to adequately protect the component for its intended use and may not guarantee excellent spray adhesion and spot weldability. pc At values greater than 80, the coating may become brittle, thereby generating powder.
[0195] In the hot stamping coated steel component according to the present invention, the coating is such that in at least one undeformed portion of the hot stamping coated steel component, and assuming that 40 ≤ E pc ≤80, the coating has a thickness greater than or equal to e depending on the undeformed part pflat Minimum crack line density dC min (e pflat ) and is defined as:
[0196]
[0197] In this expression, dC min (e pflat ) is the minimum crack line density expressed as the number of cracks per mm, and e pflat It represents the thickness of the undeformed part in mm. The crack line density dC is also the number of cracks per mm. "e" represents an exponential function.
[0198] The "crack linear density" here, which means the number of cracks per millimeter, is of course not a volume density but a linear density, because it measures how many cracks are present in a cross section of the coating over a given length in a direction parallel to the surface of the steel substrate.
[0199] In fact, the inventors conducted intensive research to solve the problem of improving spot weldability and spray adhesion, and surprisingly found that, contrary to the established belief that cracks will be detrimental to the properties of hot stamped coated steel parts, if the crack line density exceeds a threshold value, the spot weldability and spray adhesion increase dramatically together.
[0200] The inventors have also found that the relevant portion of the component with respect to crack line density is the undeformed portion, which, although it has been subjected to the same thermal cycle as the deformed portion, has not been deformed because it is located on a flange of the hot stamped component or because it is located in a flat area between two deformed portions of the component (e.g., Figure 1 In the flat top portion of the hat-shaped component shown above).
[0201] In fact, in the deformed portion, the coating undergoes deformation at the time of stamping, which will cause cracks in the coating due to the difference in expansion between the substrate and the coating and depending on the deformation temperature and the deformation rate applied at each position. However, the inventors found that having a high number of cracks in some deformed portions is not enough to ensure excellent spot weldability and excellent spray adhesion, at least because such characteristics cannot be guaranteed in other parts of the hot stamped coated steel part.
[0202] Preferably, the undeformed portion is located in the flange of the component, which is the area most likely to be subject to spot welding, so that excellent spot weldability (as well as excellent spray adhesion) is particularly desirable in this portion.
[0203] The inventors have also found that the threshold value of the crack line density is not an absolute value, but depends on the thickness of the undeformed portion, and as the thickness of the undeformed portion decreases, a higher crack line density is required to achieve desired spot weldability and spray adhesion.
[0204] As a result of these studies, the inventors found that, assuming that the coating of the component is such that 40 ≤ E pc ≤80, when the crack line density in the coating in the undeformed part is higher than or equal to dC min When it is used, excellent spot weldability and spray adhesion are achieved.
[0205] Preferably, the crack line density in the coating is kept at most 4*dC min , preferably at most 3*dC min .
[0206] Preferably, the hot stamped coated steel component comprises two or more undeformed portions, the crack line density dC(i) in each undeformed portion being higher than or equal to the thickness e of the undeformed portion. pflat (i) The associated marker is dC min (e pflat (i)) minimum crack line density.
[0207] Therefore, the undeformed portions each have a thickness e of 0.6 mm to 3.5 mm. pflat (i), i=1...n is an index associated with one of the undeformed portions, n≥2 is the number of undeformed portions, and the thickness is e pflat The crack line density dC(i) in the coating in each undeformed portion of (i) is greater than or equal to dC min (e pflat (i)), where:
[0208]
[0209] Among them, dC(i) and dC min (e pflat (i)) is expressed as the number of cracks per mm, and e pflat (i) represents the thickness in mm of the undeformed portion considered.
[0210] This formula is valid whether all undeformed parts have the same thickness or different thicknesses.
[0211] The cracks in the coating extend from the surface of the coating to a depth of at least 5 μm in a direction generally normal to the surface of the steel substrate (i.e. the interface between the steel substrate and the coating). The cracks have a width (in a direction parallel to the surface of the steel substrate) of less than 2 μm.
[0212] Cracks are thus different from possible gaps in the coating having a width greater than 2 μm, from cracks in deformations which may also have a width greater than 2 μm and from pores or coating defects affecting the coating at a depth below 5 μm.
[0213] In addition, as mentioned above, in the undeformed portion, the cracks generally have a width of at most 1 μm. In particular, the average width of the largest cracks is below 1 μm, and the largest cracks are cracks having a width greater than 90% of the widths of the cracks in the coating. In other words, among the observed cracks, 10% of the cracks having the largest width have an average crack width of less than 1 μm. The average value here means an average value calculated from the widths of all the largest cracks.
[0214] In contrast, in the deformed portion, the coating comprises more cracks having a width greater than 1 μm, which may be as large as 2 μm or even 3 μm, so that the average width of the cracks is generally greater than 1 μm. In any case, the or each deformed portion is such that the average width of the cracks having a width greater than the width of 90% of the cracks is greater than 1 μm.
[0215] Preferably, the coating in the undeformed portion does not include any gaps or cracks having a width of 2 μm or more.
[0216] The crack line density is determined as the ratio between the number of cracks observed in a cross section of the undeformed portion (in a direction parallel to the surface of the steel substrate) over a total observation length of at least 5 mm and the total length (i.e., the number of cracks divided by the total length).
[0217] In particular, the crack line density in the coating is determined by observing the cross-section of the coating of two samples taken from the undeformed part of the hot stamped coated steel part with a bright field microscope with a magnification of 500x over several fields of view, so that the total length of the field of view (in the direction parallel to the surface of the steel substrate) is at least 5 mm. The crack line density is then determined as the ratio between the number of cracks observed and the total length of the field of view.
[0218] In practice, the inventors have found that in order to ensure the desired excellent spot weldability and excellent spray adhesion, it is only necessary to have at least dC min The inventors have also found that in order to achieve these properties, a crack line density of at least dC min A crack line density is necessary.
[0219] The average width of the largest crack is determined by measuring the width of all cracks observed over the observation length, identifying the largest crack from these measurements and calculating the average of the widths of these largest cracks.
[0220] In detail, the characteristics of the coating described above are determined as follows.
[0221] First, a sample is obtained from the component and prepared.
[0222] To this end, the component was cut in the middle of its length to produce a sample of suitable dimensions of 20 x 30 mm in the undeformed part of the hot stamped coated steel component.
[0223] The cutting step is performed carefully by means of a hard iron cutting wheel (eg Struers 60A25) or preferably a micro-cutting device to avoid excessive stresses that could damage the sample.
[0224] The samples are then cleaned (preferably by an ultrasonic bath) and dried with ethanol and compressed air.
[0225] The sample is then cold mounted with resin. Cold mounting is chosen over hot mounting because the gap between the resin and the sample is very small or non-existent. This is important because the gap can be the cause of several preparation problems such as etching problems, scratches or coating damage. The resin is preferably mounted with Epofix Mixed Liquid The polymerization lasted for 10 hours. Two protective metal plates (guard plates) were placed on opposite sides of the sample in order to protect the coating from surface damage during polishing. Each time, two samples were mounted together in order to ensure that the two samples were subsequently subjected to the same polishing.
[0226] The sample is then carefully polished. The polishing step is an important step for evaluating the characteristics of the coating, as improperly performed polishing will introduce defects in the coating. These defects include accumulated diamond particles, damage in the coating such as coating flaking, and more importantly cracks in the coating, especially longitudinal cracks. Longitudinal cracks extending in a direction generally parallel to the surface of the steel substrate can reflect a preparation problem and must be avoided during polishing to ensure reliable results when counting the number of cracks.
[0227] Polishing is divided into three main stages: disc polishing, diamond polishing, and oxide polishing. The sample must be cleaned and dried after each polishing step to remove abrasive contamination and must be examined under an optical microscope.
[0228] First, the sample was polished with an abrasive disk SiC paper P320 during 120 s using a rotation speed of 150 RPM (revolutions per minute) for the sample holder and a rotation speed of 100 RPM for the disk rotating in the same direction. The force was applied at 15 N. The sample was rinsed with water.
[0229] Then, a 9 μm diamond polish is used to remove material from the surface without introducing scratches or deformation. This step is important because it ensures the flatness of the polished surface. The rotation speed is the same as the previous step, but the sample rotation is opposite to the disk rotation. The stage is set to 300 s and a force of 20 N is used. The polishing disk is damped by a lubricant at an optimal amount (0.5 mL / 30 s) to ensure better material removal. The sample is rinsed with water.
[0230] The final step was oxide polishing using colloidal silica solution (1 mL / 5 s). This step lasted 90 s at a rotation speed of 150 RPM for the sample holder and 60 RPM for the disk, rotating in the same direction. The force applied was 20 N. The sample was first cleaned with water and then with ethanol.
[0231] The samples were then etched with Nital (2% for 5 to 10 s) to reveal the steel microstructure and the steel / coating interface.
[0232] In order to determine the total coating thickness e coating and the thickness of the interdiffusion layer e IDLThe sample is imaged with a scanning electron microscope (SEM) (backscattered electron mode, magnification 500x, WD (working distance) preferably 10 mm, EHT (electron high voltage) = 15.00 kV, scale 10 microns) to show a cross-section of the coating and at least a portion of the base steel.
[0233] Based on the images, the interdiffusion layer can be identified as the light layer closest to the steel substrate.
[0234] The total thickness of the coating (including the interdiffusion layer) and the thickness of the interdiffusion layer were measured at five points horizontally spaced at 15 μm.
[0235] The total thickness of the coating and the thickness of the interdiffusion layer are then calculated as the average of the values obtained. coating and the thickness of the interdiffusion layer e IDL Hence it is the average thickness.
[0236] Furthermore, the composition of the interdiffusion layer can be determined as follows.
[0237] The samples were observed using a scanning electron microscope (SEM) to show a cross section of the coating and at least a portion of the base steel.
[0238] By energy dispersive spectroscopy (EDS), two points vertically spaced apart in the interdiffusion layer were considered at five different horizontal positions, and the composition was determined at ten points.
[0239] The composition of the interdiffusion layer was then calculated as the average of the values obtained.
[0240] If desired, the composition of the entire coating can be measured using EDS.
[0241] The determination of the crack line density in the undeformed portion of the coating is performed as follows.
[0242] Two samples mounted in the same resin were imaged using bright field optical microscopy (magnification 500x) to show cross-sections of the coating and at least a portion of the steel substrate at several locations on the sample.
[0243] Then, for each sample, ten different and non-overlapping fields of view were randomly selected and observed. Each field of view had a length of at least 250 μm (in a direction parallel to the surface of the steel substrate).
[0244] The total observation length, ie the total length of the field of view for both samples (in a direction parallel to the surface of the steel substrate) is therefore 5 mm or more (>250 μm*2*10).
[0245] In each field of view, firstly, the absence of longitudinal cracks that would extend in a direction substantially parallel to the surface of the steel substrate was verified. If longitudinal cracks were present, the field of view was ignored and replaced, since the presence of such cracks meant that the preparation (cutting, polishing) of the sample was not performed correctly at that location.
[0246] Then, in each field of view, cracks extending from the uppermost surface of the coating layer, which is generally normal to the surface of the steel substrate, in the direction of the steel substrate are identified.
[0247] In order to distinguish cracks from possible gaps in the coating, only cracks with a width of less than 2 μm are identified as cracks. Cracks with a width of 2 μm can be identified without difficulty at a magnification of 500x, but if necessary, the width of the crack can be measured as detailed below. In addition, in order to distinguish cracks from pores or coating defects, the length of the crack is measured, and only cracks with a depth of at least 5 μm (in a direction approximately orthogonal to the surface of the steel substrate) are considered as cracks.
[0248] The number of cracks was counted in each field of view, and the total number of cracks in the observed twenty fields of view was calculated.
[0249] The crack line density in the coating was then determined as the ratio between the total number of cracks and the total length of the field of view for both samples.
[0250] The determination of the average width of the largest cracks, or more generally the width of any crack, can be performed as follows.
[0251] The cross-sections for evaluating the crack line density were observed with a bright field microscope with a magnification of 500x using a camera with a resolution of 3072*2048 pixels, and the images were displayed so that one pixel of the camera was displayed as one pixel on the image. The magnification of the imaging was 3020x.
[0252] The width of each crack in all cracks in the field of view is determined.
[0253] To this end, for each crack, the width was measured at three locations located at the center of the crack and at a distance of 2 μm on each side of the center. The average of the three widths was determined as the width of the crack.
[0254] Cracks with the largest width, i.e. a width greater than 90% of the cracks in the coating, are then identified. These cracks are therefore the 10% of the cracks with the largest width. The average width of these cracks is then calculated as the sum of the individual widths of these cracks divided by the number of these cracks.
[0255] If the number of cracks is such that 90% of the number of cracks is not an integer, the result of 90% of the number of cracks is rounded to the nearest integer (e.g., 90% of 108 cracks is 97 cracks, and 90% of 135 cracks is considered to be 122 cracks).
[0256] The hot stamped coated steel component according to the invention has, at least in the undeformed portion, a welding range of more than 1 kA as measured according to standard SEP 1220-2 (2011).
[0257] The hot stamped coated steel part also has excellent spray adhesion, since at least in the undeformed portion, when subjected to dry spray adhesion and wet spray adhesion tests according to standard ISO 2409:2013, the dry spray adhesion is strictly lower than 1 and the wet spray adhesion is lower than or equal to 1.
[0258] A method according to the invention for producing a hot stamped coated steel component will now be disclosed.
[0259] The method comprises providing a steel blank having an average thickness of typically 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. This thickness is typically similar to the average thickness e of the hot stamped coated steel part to be produced from the blank. P same.
[0260] The blank comprises, on at least one face, a pre-coating of aluminium or an aluminium alloy, the pre-coating having an average thickness comprised between 19.91 μm and 40 μm.
[0261] Preferably, the blank comprises, on each of its two main faces, a pre-coating of aluminium or an aluminium alloy having an average thickness comprised between 19.91 μm and 40 μm.
[0262] The pre-coating layer may be aluminum or an aluminum alloy (containing more than 50% aluminum).
[0263] Advantageously, the pre-coating is an aluminum-silicon alloy containing by weight 7 to 15% silicon, 2 to 4% iron and optionally 0.0015 to 0.0030% calcium, the remainder being aluminum and unavoidable impurities resulting from refining.
[0264] Preferably, the pre-coat comprises by weight 8 to 11% Si, 2 to 4% Fe, optionally 0.0015 to 0.0030% Ca, the remainder being Al and impurities resulting from smelting.
[0265] The pre-coating is usually obtained by hot-dip coating in an Al or Al alloy bath.
[0266] In an embodiment, the blank is a monolithic blank, ie a blank comprising one single sub-blank obtained by cutting a pre-coated steel sheet.
[0267] The integral blank is, for example, a tailor-made rolled blank, ie a blank having a variable thickness which is obtained by differential rolling during the steel plate production process.
[0268] In another embodiment, the blank is a custom welded blank produced by assembling, in particular welding together, for example by laser welding, several blanks called sub-blanks cut from different pre-coated steel sheets.
[0269] In an embodiment, the blank has a uniform thickness of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm.
[0270] In another embodiment, the blank is a custom rolled blank or a custom welded blank, the blank having a variable thickness.
[0271] In this case, the blanks are composed of different thicknesses e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm each. Bi The blank has a given thickness e Bi Each area corresponds to the thickness of the final hot stamped coated steel part e Pi area.
[0272] In any case, the blank comprises a uniform thickness e Bflat The flat portion of the hot stamped coated steel part is designated to become the undeformed portion of the hot stamped coated steel part after the hot stamping process. Bflat It is also 0.6mm to 3.5mm, preferably 0.7mm to 3.0mm.
[0273] In other words, the thickness e Bflat It is the thickness of the portion of the blank that is transformed into the corresponding undeformed portion of the hot stamped coated steel component during hot stamping.
[0274] The thickness of this part of the blank is e Bflat Equal to the thickness e of the corresponding undeformed portion of the component pflat .
[0275] In an embodiment, the blanks include each having a uniform thickness e Bflat(i) (where i=1 . . . n, n being the number of such parts), the two or more parts being designated to become two or more undeformed parts of the hot stamped coated steel part after the hot stamping process.
[0276] Each thickness e Bflat(i)Included between 0.6 mm and 3.5 mm, preferably included between 0.7 mm and 3.0 mm. In addition, each thickness e Bflat(i) Equal to the thickness e of the corresponding undeformed portion of the component Pflat(i) .
[0277] If the thickness of the blank is uniform, the thickness e Bflat or where applicable, each thickness e Bflat(i) Equal to the thickness of the blank e B .
[0278] The blank or each sub-blank in the case where the blank is a custom welded blank is preferably made of a steel having a composition as disclosed above, in particular according to the first preferred composition, the second preferred composition or the third preferred composition. The sub-blanks may have the same steel composition or different steel compositions.
[0279] The blank or each partial blank is produced, for example, as follows.
[0280] A semi-finished product in the form of a slab, thin slab or and ingot which can be further hot rolled is provided, the semi-finished product preferably having the steel composition described above. The thickness of the semi-finished product is typically comprised between 50 mm and 250 mm.
[0281] If necessary, the semi-finished product is heated to a temperature generally comprised between 1100° C. and 1300° C. and then hot rolled at a finishing temperature preferably comprised between 880° C. and 950° C. to obtain a hot rolled steel sheet. The hot rolled steel sheet is coiled at a temperature Tc lower than or equal to 750° C. and generally higher than or equal to the Ms temperature of the steel.
[0282] At this stage, the thickness of the hot rolled steel sheet may be in a typical range of 1.5 mm to 4 mm. Depending on the thickness of the hot rolled steel sheet and the desired thickness of the sheet, the steel sheet may be pickled under usual conditions and further cold rolled or directly annealed by the process described below.
[0283] If the blank to be produced is a custom rolled blank, the steel plate can be produced by differential rolling (or continuous flexible rolling), i.e. by a process in which the plate thickness obtained after rolling is variable in the rolling direction depending on the load that has been applied to the plate by the rollers during the rolling process.
[0284] After hot or cold rolling, the steel sheet is annealed at a temperature typically comprised between Ac1 and Ac3, typically between 700°C and 850°C, to prepare for the coating and, in the case of cold rolling, to recrystallize the grains. The sheet is then hot-dipped in an Al or Al alloy bath, typically at a temperature of about 670°C to 680°C, the exact temperature depending on the composition of the bath.
[0285] The preferred pre-coating is Al-Si obtained by hot dipping the plate in a bath containing by weight 7 to 15% Si, 2 to 4% Fe, optionally 0.0015 to 0.0030% Ca, the remainder being Al and impurities resulting from smelting.
[0286] Preferably, the bath contains by weight 8 to 11% Si, 2 to 4% Fe, optionally 0.0015 to 0.0030% Ca, the remainder being Al and impurities resulting from smelting.
[0287] The pre-coated steel panels were then cooled to room temperature.
[0288] The pre-coated steel sheet is cut to obtain blanks (or sub-blanks) whose geometry is related to the final geometry of the hot stamped coated steel part.
[0289] If the blank from which the component is produced is a custom-welded blank, the sub-blanks produced therefrom are welded together as disclosed above.
[0290] In an embodiment, the sub-blanks have the same composition. In another embodiment, the compositions of the sub-blanks are different. This is particularly true if different mechanical properties are required at different locations of the final part. As an example, the composition of the steel in the first sub-blank is selected from the three preferred compositions mentioned above, and the composition of the second sub-blank is selected from two other preferred compositions or is selected within the same preferred composition as the first sub-blank but has a different specific composition.
[0291] In an embodiment, the sub-blanks have the same uniform thickness. In another embodiment, the sub-blanks have different thicknesses.
[0292] Alternatively, before the heating and hot stamping steps in the mold, the blank can be cold formed to obtain a pre-deformed blank. This cold pre-deformation makes it possible to reduce the amount of deformation in the next hot stamping step. In any case, the portion of the blank designated to become the undeformed portion of the hot stamped coated steel part after the hot stamping process is not deformed during this cold pre-deformation. Therefore, this portion of the blank remains as a flat portion. On the other hand, the portion of the blank that is then subjected to deformation in hot stamping is only partially deformed during the cold pre-deformation. Therefore, it is ensured that the cold pre-deformation has no influence on the target coating properties.
[0293] The blank (flat or cold pre-deformed) is then heated in a furnace to a temperature T comprised between 850° C. and 970° C. heat .
[0294] The heating includes a step in which the temperature of the blank is kept below the melting temperature T of the pre-coating. meltThe first heating stage and the temperature of the blank is higher than or equal to the melting temperature T of the pre-coating melt Until the heating temperature T heat The second heating stage.
[0295] The heating means is not limited and may be radiation, conduction, induction or resistance based.
[0296] The time that the blank spends during each of these two phases can be adjusted by controlling the furnace, in particular by using a furnace with different sections, each of which has independent settings, for example in terms of power and temperature, so that the heating rate can be adjusted independently of each other in each of these sections. For example, if a high heating rate is desired in the first heating phase, the first section of the furnace can be set to a high temperature and a high power to ensure this rapid heating. If a low heating rate is then desired until the final heating temperature T heat , several sections can be used, wherein the furnace temperature increases slightly from one section to another to ensure that the pre-coating is heated above the melting temperature T melt Or conversely, if it is desired to increase the melting temperature T of the pre-coating melt and heating temperature T heat If the initial short heating time is too short, a high temperature can be set in one section of the furnace, and the blank can be transferred to the target heating temperature T before reaching this temperature. heat section.
[0297] Furthermore, the skilled person knows how to determine the melting temperature of a pre-coating whose composition is known, for example using a ternary phase diagram.
[0298] The heated blank is then maintained at the heating temperature T heat in order to obtain a completely austenitic structure in the steel.
[0299] Preferably, the total residence time in the furnace including heating and holding is comprised between 1.5 min and 15 min.
[0300] The heated blank is then transferred to the die (or hot stamping press). The transfer time is preferably at most 15 s, still preferably at most 10 s or at most 8 s.
[0301] The die is then closed to stamp the blank into a component. The temperature of the blank when the die is closed is denoted as T. close .
[0302] Preferably, the time elapsed between transferring the heated blank into the mould and closing the mould is less than 8 s.
[0303] Heating and holding cause interdiffusion between the pre-coating layer and the steel substrate. In particular, during heating and holding, iron diffuses from the steel substrate toward the coating layer, and aluminum diffuses from the coating layer toward the steel substrate, and this interdiffusion causes the formation of an interdiffusion layer of the coating layer.
[0304] Additionally, depending on the composition of the pre-coating, one or more intermetallic phases may be created by interdiffusion in the form of a solid solution above the interdiffusion layer (and thus in the outer layer of the component).
[0305] According to the invention, the thickness e of the flat portion of the blank which is transformed into the undeformed portion during hot stamping is Bflat To control the heating, holding, transfer, closing and cooling of the die in order to achieve a temperature greater than or equal to dC in the coating of the undeformed portion of the hot stamped steel part min Crack line density dC.
[0306] In particular, the inventors have found that for achieving a desired crack line density in the undeformed portion of the coating, ie a crack line density dC greater than or equal to dC min The relevant factor is not the time spent in the furnace, but the temperature T of the blank when the mold is closed. close The relevant blank is above the melting temperature T of the pre-coating during hot stamping. melt The time t M .
[0307] The time t M Including the heating in the second stage mentioned above (above T melt ), at the heating temperature T heat The holding time t heat , transfer time, and the blank in the die (before and after stamping) until the formed blank reaches temperature T during cooling melt The time spent.
[0308] The time t M During the hot stamping process, the temperature of the blank can be monitored during heating and adjusted above T as detailed above. melt The time spent on heating is controlled by heat The holding time t heat And by controlling the blank during transfer to the mold and cooling to T in the mold melt The time spent during the period is determined and controlled.
[0309] The inventors have discovered that in order to obtain at least dC min Crack line density, temperature T close Must be included between 720°C and 820°C and above the melting temperature T of the pre-coating meltThe time t M Must be included in the minimum time t Mmin With the maximum time t Mmax This depends on the thickness of the flat portion of the blank designated to become the undeformed portion. Bflat , Heating temperature T heat and the melting temperature T of the pre-coating melt .
[0310] Minimum time t Mmin and the maximum time t Mmax The restrictions are as follows:
[0311]
[0312] and
[0313] In these expressions, t Mmin and t Mmax Expressed in seconds, T heat Indicates the heating temperature of the blank in °C, T melt represents the melting temperature of the pre-coating in °C, and e Bflat Indicates the thickness in mm of the flat portion of the blank which is not deformed during hot stamping and is therefore designated to become the undeformed portion of the component.
[0314] In practice, the inventors have found that meeting these conditions allows to achieve hot stamping of coated steel parts after hot stamping and cooling, such that the crack line density in the coating of the undeformed part is higher than or equal to dC min .
[0315] In contrast, when time t M The above relationship is not satisfied and / or the temperature T close Above 820°C or below 720°C, the crack line density is insufficient, making it impossible to simultaneously achieve excellent spot weldability and excellent spray adhesion.
[0316] In particular, below the minimum time t Mmin , the crack line density is insufficient, and the spray adhesion and spot weldability are not satisfactory.
[0317] On the other hand, above the maximum time t Mmin , crack line density is insufficient, and even though spray adhesion can be enhanced by longer times spent above the melting temperature, spot weldability becomes too low.
[0318] Of course, assuming t Mmin and t Mmin All depends on the heating temperature T heat , then not only time t MAnd the heating temperature T heat can be adjusted so that the time t M Included in t Mmin With t Mmin between.
[0319] In an embodiment, the blank has a uniform thickness e B , the thickness e B is then equal to the thickness e of the portion of the blank designated to become the undeformed portion of the component Bflat , t Mmin and t Mmin So it becomes:
[0320]
[0321] and
[0322] If the blank has a variable thickness, then preferably and depending on the desired properties, the time t M It can be adjusted so that the time t M Included at time t Mmin (e Bi ) and t Mmax (e Bi ) for blanks having a thickness e Bi Additional sections / areas of.
[0323] In this case, the thickness of this part of the blank can be determined according to its thickness e. Bi Calculate t for each of the considered parts Mmin and t Mmax Then, at the calculated minimum time t Mmin The maximum value and the maximum calculated time t Mmax Select the time t between the minimum values of M :
[0324] Max[t Mmin (e Bflat ),t Mmin (e Bi )…]≤t M ≤Min[t Mmax (e Bflat ),t Mmax (e Bi )…]
[0325] t Mmin and t Mmax The value of is an increasing function of thickness, which can be simplified as follows:
[0326] t Mmin (Max(e Bflat ,eBi …))≤t M ≤t Mmax (Min(e Bflat ,e Bi …))
[0327] In other words, if it is desired to ensure that the crack line density is higher than the minimum crack line density dC in two or more parts of the component produced from two or more parts of the blank having different thicknesses min , then time t M Then include the minimum time t defined for the thickest part Mmin and the maximum time t defined for the thinnest section Mmax between.
[0328] Preferably, if hot stamping is performed so that the blank has a thickness e Bflat (i) (where i=1...n) two or more portions are not deformed to produce a hot stamped coated steel part including two or more undeformed portions, then the time t M The minimum time t required to include the thickest part Mmin The maximum time t required for the thinnest part Mmax between.
[0329] t Mmin (Max(e Bflat(i) , where i = 1…n))≤t M ≤t Mmax (Min(e Bflat(i) , where i = 1…n))
[0330] In this case, it is ensured that in all considered flat portions of the blank corresponding to the undeformed portion of the component the M Production, the time t M Included in the actual thickness e corresponding to all the flat parts considered Bflat(i) The minimum time t Mmin With the maximum time t Mmax between.
[0331] Still preferably, the blank has a minimum thickness e Bmin and the maximum thickness e Bmax , time t M Included in the maximum thickness e Bmax The minimum time t required Mmin With minimum thickness e Bmin The maximum time t required Mmax between:
[0332] t Mmin (e Bmax )≤t M≤t Mmax (e Bmin )
[0333] In this case, it is ensured that all areas of the blank are M Hot stamping, time t M Included in the minimum time t corresponding to the actual thickness of all regions Mmin With the maximum time t Mmax between.
[0334] Preferably, the temperature of the blank when the mold is closed is T close is at least 740°C.
[0335] In an embodiment, the temperature T close At most 800°C.
[0336] In particular, a temperature T of up to 800°C close Allows up to 4*dC min The crack line density is reduced, thereby reducing the risk of powdering.
[0337] The heated blank is hot stamped in a die and die quenched.
[0338] In hot stamping, as detailed above, one or more portions of the blank are not subjected to deformation, and at least one portion is deformed by hot stamping.
[0339] The portion of the blank that is not subjected to deformation becomes the undeformed portion of the hot stamped coated steel component obtained by the process.
[0340] The portion of the blank that is subjected to deformation forms the deformed portion of the hot stamped coated steel component.
[0341] Due to the geometry of the final part and the forming tool, the mode and amount of deformation in the deformed part varies from one place to another. For example, some areas may be in expansion while other areas are deformed under constraint. Regardless of the deformation mode, as outlined above, the equivalent deformation ε b can be defined at each location in the press-hardened component as Among them, ε1 and ε2 are the principal deformations. Therefore, ε b represents the amount of strain introduced in each zone of the deformed part by the hot stamping process.
[0342] In the undeformed portion, the equivalent deformation is at most 0.01.
[0343] The hot stamped blank is then held within the die in order to ensure proper cooling rate and avoid part deformation due to shrinkage and phase transformation.
[0344] The hot stamped blank is cooled mainly by conduction through heat transfer with the die. The die may include a coolant circulation to increase the cooling rate or a heating box to reduce the cooling rate. Therefore, the cooling rate can be adjusted by implementing this means.
[0345] The hot stamped blank is cooled to a temperature below 400°C.
[0346] The cooling rate applied depends on the composition of the steel and the desired microstructure and mechanical properties.
[0347] From the temperature T heat The average cooling rate to 400°C (including cooling during transfer and cooling in the mould) is typically at least 27°C / s, preferably at least 50°C / s and typically below 200°C / s.
[0348] Preferably, the blank is cooled in the mould from the temperature of the blank when the mould is closed to 400° C. at an average cooling rate of at least 30° C. / s, still preferably at least 50° C. / s.
[0349] For example, if the steel has a composition according to the above-mentioned first preferred composition, the hot stamped blank is preferably first cooled in a temperature range between 750°C and 450°C at a first average cooling rate comprised between 40°C / s and 360°C / s. In this range, a transformation of austenite to martensite and possibly bainite occurs. In a further step, the hot stamped blank is cooled in a temperature range comprised between 450°C and 250°C at an average cooling rate between 15°C / s and 150°C / s, which is slower than the first cooling rate.
[0350] If the steel has a composition according to the second preferred composition, the hot stamped blank is preferably cooled in the die from the outlet of the furnace to a temperature below 400° C. at an average cooling rate of at least 30° C. / s to achieve a structure consisting essentially of martensite.
[0351] If the steel has a composition according to the third preferred composition, the hot stamped blank is preferably cooled in the die in order to obtain a structure consisting of martensite or of martensite and bainite.
[0352] In any case, the hot stamped blank is cooled within the die to a temperature below 400° C. and then cooled to room temperature to obtain a hot stamped coated steel part.
[0353] Example
[0354] Steels having compositions A, B, C and D expressed in weight percent according to Table 1 have been cut from pre-coated steel sheets having a uniform thickness e B Supplied in blank form.
[0355] The blank is pre-coated on both sides with an Al-Si pre-coating having a composition comprising 8% to 11% Si, 2% to 4% Fe, the remainder being Al and impurities resulting from smelting. The pre-coatings all have a melting temperature T of 577°C. melt .
[0356] The pre-coating thickness was adjusted in each case to a range of 19.91 μm to 40 μm, the pre-coating thickness being proportional to the thickness of the plate. B They are reported together in Table 2 below.
[0357]
[0358] Table 1
[0359] The remainder of the composition is iron and inevitable impurities (inevitable impurities include Cu, the content of Cu is reported above).
[0360] These pre-coated steel sheets have been cut into blanks.
[0361] The blank is then heated in a furnace at a temperature T heat Heat and keep at T heat and then transferred to the mold within 8 s.
[0362] The blank is then hot stamped in a die in order to form a component having a deformed portion and a flat, undeformed portion. In each case, the die is heated at a temperature T close Closed at 750℃.
[0363] The hot stamped blank is then cooled in the die to a temperature below 400° C., then removed from the die and cooled to room temperature to obtain a hot stamped coated steel part.
[0364] For each steel composition, the heating, holding, transfer and cooling in the mold were adjusted to be above the melting temperature T of the pre-coating. melt When reaching different time t M .
[0365] For each example, the blank was heated above the melting temperature T of the pre-coating. melt The time t M are reported in Table 2 and are related to the minimum time t Mmin and the maximum time t Mmax For comparison. Minimum time t Mmin and the maximum time t Mmax According to the thickness of the blank B Using the above equation, the thickness e B Equal to the thickness of that portion of the blank from which the undeformed portion is produced.
[0366]
[0367]
[0368] Table 2
[0369] The hot stamped blank is then cooled within the die to a temperature below 400° C. to achieve a hot stamped coated steel component having a martensitic structure.
[0370] Hot stamping coated steel parts with uniform thickness P , thickness e P Equal to the thickness e of the blanks used to produce these parts B (and make e P =e Pflat ).
[0371] Samples were taken from the undeformed portion of each component and prepared as described above.
[0372] The total thickness of the coating was determined using the protocol disclosed above. coating and the thickness of the interdiffusion layer e IDL and the crack line density in the coating.
[0373] The crack line density in the coating of the undeformed section was determined in each case by observing ten fields of view for each of the two samples, wherein the total observation length for both samples was 5.29 mm.
[0374] According to the above formula, the total thickness of the coating is measured by e coating and the thickness of the interdiffusion layer e IDL Determined E pc The values of are reported in Table 3 below.
[0375] Crack line density dC and minimum crack line density dC min They are also reported in Table 3.
[0376] The spray adhesion evaluation for each part was as follows.
[0377] Samples were taken from the undeformed portion of each component.
[0378] The samples were first defatted and then 5176 and surfactant were used for cleaning at 55°C for 6 minutes. The ZL6 performs with refinement.
[0379] The phosphating step was performed by immersing the sample at 50°C for 3 minutes in a R24 is achieved in a bath of a solution of TA and additives.
[0380] A 20 μm electrophoretic coating was then deposited by immersing the sample in a bath containing an aqueous solution containing Pigment W9712-N6 and Resin W7911-N6, and a nominal voltage with a voltage rise duration of 30 s was applied at 30° C., with a total duration of 180 s. The samples were then wiped and cured in an oven at 175° C. for 30 min.
[0381] The first set of samples was then subjected to a dry spray adhesion test by cross-hatching the electrophoretic coating with a cutter (scratches at 1 mm intervals), tearing the electrophoretic coating with an adhesive tape (at 460 N / m) and visually evaluating the amount of electrophoretic coating removed according to ISO 2409:2013: 0 means excellent, in other words, little or no coating was removed, and 5 means very poor, in other words, a large amount of coating (>65%) was removed.
[0382] A wet spray adhesion test was then performed on the second set of samples.The samples were immersed in a sealed box containing demineralized water at a temperature of 50°C during 10 days.
[0383] After immersion, the surface of the electrophoretic coating was cross-hatched with a cutter (scratches at 1 mm intervals), the electrophoretic coating was torn with an adhesive tape (at 460 N / m), and the amount of electrophoretic coating removed was assessed visually according to ISO 2409: 2013. Again, 0 means excellent, in other words, little or no coating was removed, and 5 means very poor, in other words, a large amount of coating (>65%) was removed.
[0384] In addition, spot weldability was evaluated by determining a welding range for each of the samples according to Standard SEP 1220-2 (2011).
[0385] For Examples 7 to 12 having a thickness of 1.2 mm, the following parameters were used:
[0386] -Electrode: F1-16-20-5.5
[0387] -Welding force: 4kN
[0388] -Welding current: medium frequency DC
[0389] -Welding time: 1 pulse of 320ms
[0390] -Hold time: 200ms
[0391] For Examples 1 to 6 having a thickness of 1.8 mm, the following parameters were used:
[0392] -Electrode: F1-20-20-8
[0393] -Welding force: 5kN
[0394] -Welding current: medium frequency DC
[0395] - Welding time: 3 pulses of 200ms (pause time 40ms)
[0396] -Hold time: 300ms
[0397] The dry spray adhesion and wet spray adhesion and welding range thus evaluated are reported in Table 3.
[0398]
[0399] Table 3
[0400] Referring to Table 2 and Table 3, Examples 2, 5, 8 and 11 are produced by the method according to the present invention and have a minimum crack line density dC greater than or equal to dC. min Crack line density.
[0401] Figure 2 The coating of Example 2 is illustrated in cross section as seen in one of the fields observed to assess crack line density. In this image, which is compared for illustration purposes only, several cracks are observed extending from the surface of the coating toward the steel substrate.
[0402] Of course, as mentioned above, the crack line density of Example 2 was not determined based on this single field of view, but was determined by observing 20 fields of view to ensure that the crack line density over a sufficient observation length was dC min (ie, 15.5 cracks / mm) or more.
[0403] In the examples of the present invention, it was observed that the cracks were generally evenly distributed in the coating in the flat, undeformed portions, which was not the case in Comparative Examples 1, 3, 4, 6, 7, 9, 10, and 12 discussed below.
[0404] These Examples 2, 5, 8 and 11 therefore have excellent dry spray adhesion, in each case below 1 and in fact 0, meaning that no or little coating was removed during the test, excellent wet spray adhesion of at most 1, and excellent spot weldability, with a welding range as wide as 1 kA.
[0405] Therefore, Examples 2, 5, 8 and 11 show that the invention has a temperature higher than or equal to dC minThe crack line density of hot stamped coated steel parts achieves excellent spray adhesion and spot weldability.
[0406] In contrast, Examples 1, 4, 7, and 10 are prepared at a time t above the melting temperature of the pre-coating layer. M These examples therefore have less than dC min Crack line density. Figure 3 An example of a field of view in a cross section of the coating in a flat, undeformed portion of Example 1 is illustrated above. In this field of view, no cracks are present in the coating. Therefore, Examples 1, 4, 7, and 10 have low spray adhesion, whether dry spray adhesion, which is always 1, or wet spray adhesion, which is higher than 1 in each case.
[0407] Examples 3, 6, 9, and 12 also have values lower than dC min Even though the dry spray adhesion is excellent and the wet spray adhesion is good for Examples 3 and 6, the spot weldability is greatly reduced compared to the parts according to the present invention due to the long time spent above the melting temperature of the coating, so these examples do achieve the purpose of the present invention.
[0408] In addition, Example 12 shows that the minimum crack line density dC for achieving this purpose min It does depend on the thickness. In particular, this example shows, by comparison with Examples 2 and 5, that if the component has a thickness of 1.2 mm, it is not sufficient to have a crack line density of, for example, 15.5 / mm as in Example 12, but in contrast, for a higher thickness of 1.8 mm as in the case of Examples 2 and 5, it allows the target characteristics to be achieved.
[0409] The example thus confirms that if the undeformed portion of the component is such that its coating has a value greater than or equal to dC min If the crack line density is less than 0.05, excellent spot weldability and excellent spray adhesion are achieved at least in this portion.
[0410] In addition, the example shows that by adjusting the process so that the temperature T close The time that the blank spends above the melting temperature of the coating is properly controlled, and the desired sufficient crack line density and therefore the desired properties can be achieved.
[0411] The steel components produced according to the invention can therefore advantageously be used for producing chassis or body-in-white components or suspension arms for motor vehicles.
Claims
1. A hot stamping coated steel component, comprising a steel substrate and an aluminum alloy coating on at least one surface of the steel substrate, wherein the coating comprises an interdiffusion layer and an outer layer in order from the steel substrate outward, wherein: The total thickness of the coating is coating and the thickness of the interdiffusion layer e IDL The following conditions are met: 40≤E pc ≤80 in e IDL represents the thickness of the interdiffusion layer in μm, and e coating represents the total thickness of the coating in μm, And wherein the hot stamping coated steel component comprises a thickness e of 0.6 mm to 3.5 mm. Pflat an undeformed portion and at least one deformed portion, the crack line density dC in the coating in the undeformed portion being higher than or equal to the minimum crack line density dC min (e Pflat ), the minimum crack line density dC min (e Pflat ) is limited to: Among them, dC and dC min (e Pflat ) is expressed as the number of cracks per mm, and e pflat Denote the thickness of the undeformed portion in mm.
2. The hot stamped coated steel component according to claim 1, wherein: The crack line density dC in the coating in the undeformed portion is lower than or equal to 4*dC min (e Pflat ).
3. The hot stamped coated steel component according to any one of claims 1 or 2, wherein: The hot stamped coated steel component has a uniform thickness e comprised between 0.6 mm and 3.5 mm P .
4. The hot stamped coated steel component according to any one of claims 1 or 2, wherein: The hot stamped coated steel component has a variable thickness, the hot stamped coated steel component including components having different thicknesses each comprised between 0.6 mm and 3.5 mm. Pi The hot stamped coated steel component has an average thickness e comprised between 0.6 mm and 3.5 mm. P .
5. The hot stamped coated steel component according to any one of claims 1 to 4, wherein: The hot stamped coated steel parts include a plurality of steel parts each having a thickness of 0.6 mm to 3.5 mm. pflat (i), the crack line density dC(i) in the coating in each of the undeformed portions being greater than or equal to dC min (e pflat (i)), where: Among them, e pflat (i) denotes the thickness of the undeformed portion under consideration expressed in mm, where i=1...n, n≥2, and dC(i) and dC min (e pflat (i)) is expressed as the number of cracks per mm and represents the thickness e pflat The crack line density and the minimum crack line density in the coating in the considered undeformed portion of (i).
6. The hot stamped coated steel component according to any one of claims 1 to 5, wherein: In cross section, cracks in the coating of the undeformed portion extend from an uppermost surface of the coating toward the steel substrate over a depth of at least 5 μm in a direction substantially normal to the surface of the steel substrate, the cracks each having a width of less than 2 μm in a direction substantially parallel to the surface of the steel substrate.
7. The hot stamped coated steel component according to any one of claims 1 to 6, wherein: The crack line density is determined as the ratio between the total number of cracks observed in several cross sections of the undeformed portion over a total observation length of at least 5 mm in a direction parallel to the surface of the steel substrate using a bright field optical microscope and the total observation length.
8. The hot stamped coated steel component according to any one of claims 1 to 7, wherein: The hot stamped coated steel component is an integral component, or a hot stamped welded component including at least two hot stamped coated sub-components and at least one hot stamped weld that combines the hot stamped coated sub-components together.
9. The hot stamped coated steel component according to claim 8, wherein: The hot stamped coated steel component or each hot stamped coated subcomponent has a structure comprising by volume at least 60% martensite, at most 20% bainite, at most 5% ferrite and at most 15% austenite.
10. The hot stamped coated steel component according to any one of claims 8 or 9, wherein: The steel in the hot stamped coated steel component or each hot stamped coated subcomponent has a chemical composition comprising, in weight %: 0.062%≤C≤0.4% 0.4%≤Mn≤3.9% 0.10%≤Si≤1.5% 0.005%≤Al≤1.0% 0.001%≤Cr≤2.0% 0.001%≤Ti≤0.2% 0.0005%≤B≤0.010% Ni≤2% Nb≤0.1% Mo≤0.65% W≤0.30% N≤0.010% 0.0001%≤S≤0.05% 0.0001%≤P≤0.1% Ca≤0.005% The balance of the composition comprises iron and unavoidable impurities resulting from refining.
11. The hot stamped coated steel component according to claim 10, wherein: The steel in the hot stamped coated steel component or at least one hot stamped coated subcomponent has a chemical composition comprising in weight %: 0.062%≤C≤0.095% 1.4%≤Mn≤1.9% 0.2%≤Si≤0.5% 0.020%≤Al≤0.070% 0.02%≤Cr≤0.1% Among them, 1.5%≤(C+Mn+Si+Cr)≤2.7% 0.0035%≤Ti≤0.072% 0.0002%≤B≤0.004% 0.04%≤Nb≤0.06% Among them, 0.044%≤(Nb+Ti)≤0.09% 0.001%≤N≤0.009% 0.0005%≤S≤0.003% 0.0001%≤P≤0.020% Ca≤0.005%, The balance of the composition comprises iron and unavoidable impurities resulting from refining.
12. The hot stamped coated steel component according to claim 10, wherein: The steel in the hot stamped coated steel component or at least one hot stamped coated subcomponent has a chemical composition comprising in weight %: 0.15%≤C≤0.30% 0.5%≤Mn≤3.0% 0.10%≤Si≤0.50% 0.005%≤Al≤0.1% 0.01%≤Cr≤1.0% 0.001%≤Ti≤0.2% 0.0002%≤B≤0.010% 0.0005%≤N≤0.010% 0.0001%≤S≤0.05% 0.0001%≤P≤0.1% Ca≤0.005% The remainder is Fe and unavoidable impurities resulting from refining.
13. The hot stamped coated steel component according to claim 10, wherein: The steel in the hot stamped coated steel component or at least one hot stamped coated subcomponent has a chemical composition comprising, in weight %: 0.3%≤C≤0.4% 0.5%≤Mn≤1.0% 0.40%≤Si≤0.80% 0.01%≤Al≤0.1% 0.1%≤Cr≤1.0% 0.008%≤Ti≤0.03% 0.0005%≤B≤0.003% Ni≤0.5% 0.01%≤Nb≤0.1% 0.1%≤Mo≤0.5% N≤0.005% 0.0001%≤S≤0.004% 0.0001%≤P≤0.02% Ca≤0.0010% The balance of the composition comprises iron and unavoidable impurities resulting from refining.
14. A method for producing a hot stamped coated steel part, the method comprising the following consecutive steps: - Provide an average thickness of e B a steel blank of 0.6 to 3.5 mm, said steel blank comprising, on at least one face, a pre-coating of aluminium or an aluminium alloy, said pre-coating having an average thickness comprised between 19.91 μm and 40 μm, - Heating the steel blank in a furnace to a heating temperature T comprised between 850° C. and 970° C. heat , and the steel blank is maintained at the heating temperature T heat in order to obtain a completely austenitic structure in the steel of the blank, - transferring the heated blank to a mold and then closing the mold, - hot stamping the blank in the die so as to have a thickness e Bflat A flat portion of the blank having a thickness of 0.6 mm to 3.5 mm is not subjected to deformation, and at least a portion of the blank is deformed by hot stamping, thereby obtaining a hot stamped blank comprising an undeformed portion and at least one deformed portion, - cooling the hot stamped blank to a temperature of less than 400° C. to obtain a hot stamped coated steel part, in, When the mold is closed, the temperature of the blank is T close Included between 720°C and 820°C, and during heating, holding, transfer and hot stamping, the blank is above the melting temperature T of the pre-coating layer. melt The time t M Included in the minimum time t Mmin With the maximum time t Mmax Between, among which: and Among them, t Mmin and t Mmax Expressed in seconds, T heat represents the heating temperature of the blank in °C, T melt represents the melting temperature of the pre-coating in °C, and e Bflat It indicates the thickness of the portion of the blank not subjected to deformation in mm.
15. The method according to claim 14, wherein: The pre-coating layer is an aluminum alloy pre-coating layer comprising by weight: 7% to 15% silicon, 2% to 4% iron and optionally 0.0015% to 0.0030% calcium, the remainder being aluminum and unavoidable impurities.
16. The method according to claim 15, wherein: The pre-coating is an aluminum alloy pre-coating comprising by weight: 8% to 11% silicon, 2% to 4% iron, optionally 0.0015% to 0.0030% calcium, the remainder being aluminum and unavoidable impurities.
17. The method according to any one of claims 14 to 16, wherein: When the blanks are hot stamped in the die, each of the blanks has a thickness e of 0.6 mm to 3.5 mm. Bflat The two or more flat portions of (i) are not subjected to deformation, and the blank is subjected to deformation at a temperature above the melting temperature T of the pre-coating layer. melt The time t M The minimum time t required to include the flat portion with the maximum thickness Mmin (Max(e Bflat(i) ) and the maximum time t required for the flat portion with the minimum thickness Mmax (Min(e Bflat(i) )between.
18. The method according to any one of claims 14 to 17, wherein: When the blank is hot stamped in the die, the blank has a minimum thickness e Bmin To the maximum thickness e Bmax The blank has a variable thickness within a range of 100°, and the blank is formed at a temperature above the melting temperature T of the pre-coating. melt The time t M Included in the maximum thickness e Bmax The minimum time t required Mmin (e Bmax ) and the minimum thickness e Bmin The maximum time required t Mmax (e Bmin )between.
19. The method according to any one of claims 14 to 18, wherein: The steel billet is a whole billet, a customized rolled billet, or a customized welded billet produced by welding at least two sub-billets together.
20. The method according to claim 19, wherein: The blank or each sub-blank is produced by cutting a pre-coated steel sheet having a chemical composition comprising, in wt. %: 0.062%≤C≤0.4% 0.4%≤Mn≤3.9% 0.10%≤Si≤1.5% 0.005%≤Al≤1.0% 0.001%≤Cr≤2.0% 0.001%≤Ti≤0.2% 0.0005%≤B≤0.010% Ni≤2% Nb≤0.1% Mo≤0.65% W≤0.30% N≤0.010% 0.0001%≤S≤0.05% 0.0001%≤P≤0.1% Ca≤0.005% The balance of the composition comprises iron and unavoidable impurities resulting from refining.
21. The method according to claim 20, wherein: The chemical composition of the blank or at least one sub-blank comprises in weight % the following: 0.062%≤C≤0.095% 1.4%≤Mn≤1.9% 0.2%≤Si≤0.5% 0.020%≤Al≤0.070% 0.02%≤Cr≤0.1% Among them, 1.5%≤(C+Mn+Si+Cr)≤2.7% 0.0035%≤Ti≤0.072% 0.0002%≤B≤0.004% 0.04%≤Nb≤0.06% Among them, 0.044%≤(Nb+Ti)≤0.09% 0.001%≤N≤0.009% 0.0005%≤S≤0.003% 0.0001%≤P≤0.020% Ca≤0.005%, The balance of the composition comprises iron and unavoidable impurities resulting from refining.
22. The method according to claim 20, wherein: The chemical composition of the blank or at least one sub-blank comprises in weight % the following: 0.15%≤C≤0.30% 0.5%≤Mn≤3.0% 0.10%≤Si≤0.50% 0.005%≤Al≤0.1% 0.01%≤Cr≤1.0% 0.001%≤Ti≤0.2% 0.0002%≤B≤0.010% 0.0005%≤N≤0.010% 0.0001%≤S≤0.05% 0.0001%≤P≤0.1% Ca≤0.005% The remainder is Fe and unavoidable impurities resulting from refining.
23. The method according to claim 20, wherein: The chemical composition of the blank or at least one sub-blank comprises in weight % the following: 0.3%≤C≤0.4% 0.5%≤Mn≤1.0% 0.40%≤Si≤0.80% 0.01%≤Al≤0.1% 0.1%≤Cr≤1.0% 0.008%≤Ti≤0.03% 0.0005%≤B≤0.003% Ni≤0.5% 0.01%≤Nb≤0.1% 0.1%≤Mo≤0.5% N≤0.005% 0.0001%≤S≤0.004% 0.0001%≤P≤0.02% Ca≤0.0010% The balance of the composition comprises iron and unavoidable impurities resulting from refining.
24. The method according to any one of claims 19 to 23, wherein: Providing the blank or each sub-blank comprises the following successive steps: - Supply of semi-finished steel products, - optionally, reheating the semi-finished product to a temperature between 1100° C. and 1300° C., - hot rolling the semi-finished product to obtain a hot-rolled steel plate, - coiling the hot rolled steel sheet at a coiling temperature lower than or equal to 750° C., - Optionally, pickling the hot rolled steel sheet, -optionally, the hot rolled steel sheet is cold rolled to obtain a cold rolled steel sheet, - heating the hot-rolled steel sheet or the cold-rolled steel sheet to an annealing temperature between Ac1 and Ac3, - hot-dip coating of the steel sheet in an aluminum or aluminum alloy bath at a temperature of 670° C. to 680° C., - Cool the pre-coated steel sheet to room temperature, - cutting the pre-coated steel sheet to obtain the blanks or sub-blanks, - Optionally, the sub-blanks are welded together to produce a custom welded blank.
25. Use of a hot stamped coated steel part according to any one of claims 1 to 13 or produced by a method according to any one of claims 14 to 24 for the manufacture of chassis or body-in-white parts or suspension arms for motor vehicles.
Citation Information
Patent Citations
Hot-rolled and coated steel sheet for hot-stamping, hot-stamped coated steel part and methods for manufacturing the same
CN109982839A
Zinc-coated steel sheet with high resistance spot weldability
CN110892087A
Method for producing a coated flat steel product and coated flat steel product
CN112789358A
A press hardened part with high resistance to delayed fracture and a manufacturing process thereof
CN112955572A
Steel sheet for hot pressing and method for producing same
CN114127324A